A Welcoming Wilderness: The Role of Wild Berries in the Construction of Newfoundland and Labrador as a Tourist Destination - Everett, Holly (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2007)
AbstractWild berries have long been integral to Newfoundlanders’ and Labradorians’ food stores. Berry picking remains an important late summer and early fall activity, combining traditional, geographical knowledge with material culture, foodways and custom. Berries may also be Newfoundland and Labrador’s most successful culinary tourism product to date, combining attributes of health, wilderness and resourcefulness. Whereas ethical and moral uncertainty or conviction precludes many tourists from trying seal products, and health concerns prevent the enjoyment of regional favorites such as fish and chips, berries offer visitors a window into local culture beyond reproach. Reifying the text and images of national and provincial tourist literature emphasizing the area’s “outdoor nature product,” the berries serve as an iconic image of a resourceful people intimately connected to a bountiful, welcoming wilderness.